2020
DOI: 10.3390/geosciences10040132
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Properties of Fly-Ash-Stabilized Sands

Abstract: The stabilization of soil through the addition of fly ash has been shown to be an effective alternative for improving the strength and stiffness of soil through the resulting chemical reactions. The chemical reaction that occurs dissociates the lime (CaO) in the fly ash, and the establishment of cementitious and pozzolanic gels (consisting of calcium silicate hydrate (CSH) gel and calcium aluminate hydrate (CAH) gel) binds the soil particles and increases the strength and stiffness of the soil. Investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 46 publications
2
21
0
3
Order By: Relevance
“…The Si and Al minerals found in industrial by-products such as fly ash from coal combustion and GGBFS from iron combustion are employed in geopolymer processes for soil stabilization [ 57 , 58 , 59 , 60 ]. In order to produce geopolymer, the sources of alumina and silica (fly ash and GGBFS) act as precursors that are easily dissolved in alkaline solutions resulted from alkaline activation, making geopolymerization possible [ 47 , 49 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Si and Al minerals found in industrial by-products such as fly ash from coal combustion and GGBFS from iron combustion are employed in geopolymer processes for soil stabilization [ 57 , 58 , 59 , 60 ]. In order to produce geopolymer, the sources of alumina and silica (fly ash and GGBFS) act as precursors that are easily dissolved in alkaline solutions resulted from alkaline activation, making geopolymerization possible [ 47 , 49 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adhikari et al [55] concluded that geopolymer reaction was a progressive and continuous process, that generally continues for extended period of time, while being responsible for continued strength gain of the stabilized soil. Simatupang et al [56] specifically stated that the strength gain was delayed at the beginning of the curing period (particularly at a curing time of less than 28 days) and that more time was required for the pozzolanic reaction to form cementitious compounds in the FA stabilized soil. Teing et al [49] mentioned that the delayed pozzolanic activity was due to the low reactivity of the silica and alumina present within the FA, which caused FA treated specimens for short curing periods to have low to moderate strength gain.…”
Section: Unconsolidated Undrained (Uu) Triaxial Compression Testmentioning
confidence: 99%
“…Dewasa ini, fly ash telah dimanfaatkan dalam berbagai bidang konstruksi bangunan sipil, seperti dalam stabilisasi tanah [8], [9], [11], [12]. Stabilisasi tanah dengan fly ash telah diterapkan sebagai alternatif yang efektif untuk peningkatan kekuatan dan kekakuan tanah melalui reaksi kimia [13], [14].…”
Section: Pendahuluanunclassified